Analisis Return Saham Sebelum Dan Sesudah Pengumuman Right Issue Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia (Tahun 2020–2024) - Muliyani Wahyuni; Endang Kartini; Rusdi (Akuntabel: Jurnal Ilmiah Akuntansi, 2026)
This study aims to analyze the differences in stock returns before and after the announcement of rights issues in banking companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The research employed an event study method with an observation window of 11 days, comprising 5 days before and 5 days after the announcement. The sample was selected using purposive sampling, resulting in 19 banking companies that met the criteria. The data consisted of daily stock prices, which were then used to calculate actual returns. They were tested using the paired-samples t-test when the data were normally distributed, or the Wilcoxon signed-rank test when they were not. The results show no significant difference in stock returns before and after the announcement of rights issues. This indicates that the market did not respond meaningfully to the announcement of rights issues. The findings imply that investors should pay greater attention to companies' fundamental information and long-term prospects when making investment decisions.